A national survey of renal replacement therapy prescribing practice for acute kidney injury in Malaysian intensive care units - Jamal, Janatltul Ain; Mat Nor, Mohd Basri; Mohamad Nor, Fariz Safhan; Udy, Andrew A Udy; Lipman, Jeffrey; Roberts, Jason A. (Asian Pacific Society of Nephrology, 2014)
Objectives: To describe renal replacement therapy (RRT) prescribing practices in Malaysian intensive care units (ICU), and compare this with previously published data from other regions. Method: A survey was sent to physicians responsible for prescribing RRT in major ICU throughout Malaysia. The questionnaire sought information on the physicians' background, and detailed information regarding RRT settings. Results: Nineteen physicians from 24 sites throughout Malaysia responded to the survey (response rate 79.2%). Sixteen respondents were intensivists (84%), 2 were anaesthetists (11%) and one was a nephrologist (5%). The majority (58%) used continuous venovenous haemofiltration (CVVH) as the treatment of choice for acute kidney injury (AKI) in critically ill patients. RRT prescription was predominantly practitioner-dependent (63%), while 37% reported use of a dedicated protocol. The mean blood flow rate and effluent flow rate used for continuous RRT (CRRT) were 188.9 ± 28.9 mL/min and 30.6 ± 4.7 mL/kg/h respectively. Replacement fluid solutions containing both lactate and bicarbonate were commonly used during CRRT, applied both pre- and post-dilution. Conclusion: CRRT was the first-choice modality used to treat AKI in critically ill patients. CVVH was the most common CRRT technique used, while other RRT modalities were used less frequently. Overall, RRT practices were similar to those observed in other regions, although the modality and settings used were slightly different, likely due to local availability.